2011
DOI: 10.1002/cncy.20140
|View full text |Cite
|
Sign up to set email alerts
|

p16/ki‐67 dual‐stain cytology in the triage of ASCUS and LSIL Papanicolaou cytology

Abstract: BACKGROUND:The objective of this study was to analyze the diagnostic performance of a newly established immunocytochemical dual‐stain protocol, which simultaneously detects p16INK4a and Ki‐67 expression in cervical cytology samples, for identifying high‐grade cervical intraepithelial neoplasia (CIN2+) in women with Papanicolaou (Pap) cytology results categorized as atypical squamous cells of undetermined significance (ASCUS) or low‐grade squamous intraepithelial lesions (LSIL).METHODS:Residual liquid‐based cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(117 citation statements)
references
References 25 publications
8
108
0
1
Order By: Relevance
“…All cases of CIN2 or CIN3 that were histologically confirmed postpartum were identified by a positive dual-stained cytology result, while the test had a high specificity using the same CIN2+ threshold. These results are in accordance with previous studies, which have shown that dual-stained cytology combines both high sensitivity and high specificity for the detection of underlying high-grade cervical intraepithelial neoplasia [8,10,11,14]. …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…All cases of CIN2 or CIN3 that were histologically confirmed postpartum were identified by a positive dual-stained cytology result, while the test had a high specificity using the same CIN2+ threshold. These results are in accordance with previous studies, which have shown that dual-stained cytology combines both high sensitivity and high specificity for the detection of underlying high-grade cervical intraepithelial neoplasia [8,10,11,14]. …”
Section: Discussionsupporting
confidence: 82%
“…Several recent studies have shown that p16/Ki-67 positivity is strongly associated with the presence of transforming HPV infections and histologic abnormalities [8,9,10,11,12,13,14]. To date, there are no data on the efficiency of this new diagnostic tool in prenatal care.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies that evaluated immunostaining for p16 tumor suppressor protein as a surrogate biomarker for the presence of highrisk HPV in cytology smears that had subsequent CIN 2ϩ or CIN 3ϩ biopsy results have shown that performance characteristics were not sufficient to add value as a triage test (87,(114)(115)(116). Other biomarkers, such Ki-67 to detect deregulated cell cycle proliferation, dual staining for Ki-67 plus p16, and BD ProEx C (Becton, Dickinson and Company, Franklin Lakes, NJ) to detect aberrant S-phase induction, genes with aberrant DNA methylation, and chromosomal aberrations in the telomerase RNA gene have not proven useful, or there is insufficient evidence related to the clinical value of the test (117)(118)(119)(120)(121)(122)(123). Further, the leading medical professional societies have not recommended these tests in their cervical cancer screening guidelines.…”
Section: Commercially Available Test Systems For Hpv Detection In Thementioning
confidence: 99%
“…MIB-1 complements p16 INK4A in the analysis of histological sections by differentiating SIL from atrophic epithelium with atypia [24]. Its complementary role to p16 INK4A in cytology has also been tested [16,30,33,35,36] and is discussed below.…”
Section: What Are the Main Goals For Immunomarkers?mentioning
confidence: 99%
“…The authors found the combination of p16 INK4a and MIB-1 useful for the management of women with equivocal cytology. Evidence from these studies resulted in the development of an ICC dual-stain protocol, which simultaneously detects p16 INK4A and Ki-67 expression in cervical cytology samples [36,65]. The p16 INK4A /Ki-67 dual stain was tested on ASC-US/LSIL cases for HSIL identification, and immunostain positivity was scored independently of the interpretation of cytomorphological abnormalities.…”
Section: Markers Tested In Series and Combinationmentioning
confidence: 99%